France’s Foreign Policy on Russia - Ukraine Conflict a Review with Poliheuristic Theory - Fathun, Laode Muhamad; Sinambela, Stivani Ismawira; Rahmalia, Alfiyah Nur; Nurlaela, Della; Abdullah, Husain; Lumumba, Patrice (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2025)
The present study aims to identify and analyse the rational factors considered by France in responding to the conflict between Russia and Ukraine. In response, France pursued a rational foreign policy, taking into account a number of factors, both national and personal. The present study employs a qualitative research method, adopting a case study approach. The present study employs secondary data and a process of literature review. The analysis of data is a process which encompasses two fundamental techniques: data sufficiency and testing processes. This study employs a comprehensive literature review to identify discrepancies and variations with previous research. The findings of this study demonstrate that the factors considered in French foreign policy are cognitive psychology and rational calculation. These two elements were analysed and became the primary considerations for France in formulating policies to support Ukraine over Russia. This was deduced from meticulous calculations in the disciplines of economics, politics and security. The calculations demonstrated that France's foreign policy was characterised by a high degree of rationality, underscoring the substantial ramifications of the decision to abstain from providing support to Ukraine. France has the prerogative to disregard specific non-compensatory factors, even if these factors ultimately prove advantageous to France. For instance, there are economic advantages to be gained, particularly in the context of collaboration with Russia. Consequently, this research will be of particular interest to scholars in the field of foreign policy.